Naming and Branding of Madurese Traditional Culinary - Ekawati, Rosyida; Ayuningtiyas, Diah Ikawati (Universitas Airlangga, 2024)
Madura has diverse culinary specialties. This aspect of culinary naming and branding is interesting to study in relation to culinary tourism. This study aims to explain aspects of food naming and their patterns in traditional Sumenep culinary delights. In addition, it also explains the branding aspects of the food. Data on food names were obtained from the official tourism guidebook issued by the Office of Culture, Youth, Sports, and Tourism of Sumenep Regency. The results of this research show that aspects of food naming are derived from the food ingredients used, the uniqueness of the food, and the culinary origin, emphasizing its origin from Madura. The food naming uses patterns of words and phrases. If it is used a single word then the name of the food is unique, and if it is used a phrase pattern then the second word explains the first word, either for material or origin. Meanwhile, the culinary branding aspect in the tourist guidebook is to use explanations of authentic, distinctive, easy to find, delicious, affordable prices and cultural heritage. The terms used provide a positive image for traditional Madurese culinary delights.